Women’s marginalization in the novel Racun Puan and its relevance to critical literacy in Indonesian language learning at senior high school - Ananda Nur Aprilia Ika Widyaningsih; Ali Imron Al-Ma'ruf; Main Sufanti (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
This research was conducted because Ni Nyoman Ayu Suciartini's novel Racun Puan presents the issue of gender inequality. In addition, there has been no study related to the marginalization of women in the novel. The purpose of this study is to describe the forms of marginalization of women in the novel and to provide teaching materials to strengthen critical literacy in Indonesian language learning. The method used in this study is qualitative descriptive. The data used consists of quotes that reflect the marginalization of women, with the data sources taken from the novel Racun Puan by Ni Nyoman Ayu Suciartini. Data in the form of information about the use of marginalization in the novel as teaching materials for critical literacy, with data sources from peers and teachers at SMA N 1 Jatinom. Data collection techniques included literature study, questionnaires, and interviews. Data analysis, using semiotic reading methods and interactive models. The results of the study were (1) forms of marginalization of women in the form of control over their right to express their opinions, their movements, and their social relationships (2) as teaching materials for strengthening critical literacy in Indonesian language learning.